A mixed method study of self- and peer-assessment: Implications of grading online writing assignments on scientific news literacy. Issue 1 (2nd January 2021) - Zakharov, Wei; Li, Haiyan; Fosmire, Michael; Pascuzzi, Pete E.; Harbor, Jon
Abstract: The current dynamic information environment allows readers to access a vast amount of content, but of varied quality. Information professionals increasingly should promote students' scientific news literacy and critical thinking skills. The challenge for instructors, however, is to assess and provide constructive feedback on writing assignments, especially in large-scale online classes. Online peer-assessment tools can facilitate reliable self- and peer-assessment in scientific literacy education at scale. This mixed method study empirically examines differences between self- and peer-assessment and inter-rater reliability among peer assessors and investigates patterns of discrepancies in grading.